Healthcare Workers and Burnout During COVID-19 Pandemic - Upadhyay, Preeti (Journal of Lumbini Medical College, 2020)
Have you ever felt stuck? Or rather unmotivated and unsatisfied at your work? Maybe you do not feel like being a doctor anymore, but the fear of what will you do after; scares you more. Or maybe, you do wish to continue your medical practices but feel rather tired and let down at most times. In either scenario, you are not alone. Several healthcare workers feel under-appreciated and suffer from lack of enthusiasm for work, feelings of cynicism towards life and low sense of personal accomplishment, in short, they feel “Burnt out”. Burnout is on the rise in medical fraternity. Established professionals, residents in training, to young medical school trainees beginning their careers in medicine, none can escape from the brunt of burnout. Long working hours and increasing burden of bureaucratic tasks make the medical profession a tedious one. Continued exposure to human suffering and death introduces cynicism towards life and its purpose. Constant need to be compassionate to patients and their family members require immense mental and emotional fortitude. However, with an increase in violence against the medical fraternity, a typical doctor begins to question the sanctity of the profession and feels unappreciated.